Dry Reforming of Methane Over Oil Palm Shell Activated Carbon and ZSM-5 Supported Cobalt Catalysts - Izirwan, Izhab; Nor Aishah, Saidina Amin; Mohd, Asmadi (Taylor & Francis, 2017)

(untitled)
In this study, cobalt supported oil palm shell activated carbon (Co/OPS-AC) and ZSM-5 zeolite (Co/ZSM-5) catalysts have been prepared for dry reforming of methane. Cobalt ratios of 6.0 and 14.0 wt% were deposited via wet impregnation method to the OPS-AC and ZSM-5 catalysts. The catalysts were characterized by XRD, N2 adsorption--desorption isotherms, BET surface area, SEM, FESEM-EDX, TPR-H2, and TPD-NH3. The dry reforming of methane was performed using a micro reactor system under the condition of 10,000 ml/h.g-cat, 3 atm, CH4/CO2 ratio of 1.2:1.0 and temperature range from 923 K to 1023 K. The gaseous products were analyzed by gas chromatography (GC) with thermal conductivity detector (TCD) and further quantified to determine the conversions of CH4 and CO2, and the yields of CO and H2. Experimental results revealed both catalysts exhibited lower conversions of CO2 and CH4 with the increase in temperature from 923 K to 1023 K. The reduced conversions may be due to the formation of carboneous substance on the catalyst known as coking. Comparatively, Co/OPS-AC gave higher conversions of CO2 and CH4 as well as higher yields of H2 and CO as it has a higher surface area than Co/ZSM-5 which subsequently rendered higher activity for the reforming of methane. With the increasing cobalt loadings and reaction temperature, OPS-AC(14) catalyst exhibited improved activity and H2/CO ratio. Based on these results, cobalt supported OPS activated carbon catalyst was suggested to be more effective for CO2 and CH4 conversions.